The Influence of Work Discipline and Teamwork on Employee Job Satisfaction - Sahyunu (International Journal of Management and Education in Human Development, 2022)
The objectives to be achieved in this study are to Test and explain the simultaneous influence of Work Discipline and Teamwork on the Job Satisfaction of Employees of Basarnas Kendari. Examine and explain the effect of work discipline on the performance of employees of Basarnas Kendari. Testing and explaining the impact of teamwork on the job satisfaction of Basarnas Kendari employees. The population in the study are all Agency Sar National Kendari, which overall is an employee of domestic civil (PNS), which amounted to as many as 114 Employees. Measurement of data in this study using a Likert scale. The data analysis technique used in this study was descriptive statistical data analysis and inferential statistics, namely multiple linear regression analysis using SPSS Version 20 software. Based on the data analysis, the results showed that Work Discipline and Teamwork Significantly affect the Job Satisfaction of Employees Basarnas Kendari. Work Discipline has a positive and significant effect on Employee Job Satisfaction. Teamwork has a positive impact on employee job satisfaction.